Physical boundaries within aggregates – differences between amorphous, para‐crystalline, and crystalline Structures. Issue 11 (November 2015) - Albers, Peter; Maier, Monika; Reisinger, Martin; Hannebauer, Bernd; Weinand, Rudolf
Abstract : SEM images of isolated aggregates of silica and titania show structural similarities at the several hundred nanometer scale (red). However, high resolution TEM reveals distinct differences of the interior structure down to the nanoscale. Pyrogenic titania entities are formed by intergrown crystallites (blue). Grain or solid phase boundaries are detected. Synthetic silicas of different production technology are completely amorphous (green) and, thus, the aggregate is the constituent particle. This conclusion is confirmed by 3D‐TEM investigations. (Picture: P. Albers et al., 10.1002/crat.201500040 pp. 846–865, in this issue)